Un-Balanced Economic Growth - LEUNG, Hing-Man (Institutional Knowledge at Singapore Management University, 2007)
Since the elasticity of substitution between capital and labor is not always one, and since technical progress is not always Harrod-neutral, it is desirable to have an endogenous growth model that admits all sizes of the elasticity and all known technology modes. We derive an equation to do just that, fully describing the per capita income growth rate at all times. It shows a typical economy needing hundreds if not thousands of years to reach its long term growth rate, leading to the conclusion that even the short run may be very long indeed.